Molecular Cloning and Expression Analysis of the Mitochondrial Pyruvate Dehydrogenase from Maize - Thelen, Jay J. (American Society of Plant Physiologists, 1999)
Four cDNAs, one encoding an α-subunit and three encoding β-subunits of the mitochondrial pyruvate dehydrogenase, were isolated from maize (Zea mays L.) libraries. The deduced amino acid sequences of both α- and β-subunits are approximately 80% identical with Arabidopsis and pea (Pisum sativum L.) homologs. The mature N terminus was determined for the β-subunit by microsequencing the protein purified from etiolated maize shoot mitochondria and was resolved by two-dimensional gel electrophoresis. This single isoelectric species comprised multiple isoforms. Both α- and β-subunits are encoded by multigene families in maize, as determined by Southern-blot analyses. RNA transcripts for both α- and β-subunits were more abundant in roots than in young leaves or etiolated shoots. Pyruvate dehydrogenase activity was also higher in roots (5-fold) compared with etiolated shoots and leaves. Both subunits were present at similar levels in all tissues examined, indicating coordinated gene regulation. The protein levels were highest in heterotrophic organs and in pollen, which contained about 2-fold more protein than any other organ examined. The relative abundance of these proteins in nonphotosynthetic tissues may reflect a high cellular content of mitochondria, a high level of respiratory activity, or an extra plastidial requirement for acetate.